If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -13 = 4x Reorder the terms: -13 + 5x = 4x Solving -13 + 5x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -13 + 5x + -4x = 4x + -4x Combine like terms: 5x + -4x = 1x -13 + 1x = 4x + -4x Combine like terms: 4x + -4x = 0 -13 + 1x = 0 Add '13' to each side of the equation. -13 + 13 + 1x = 0 + 13 Combine like terms: -13 + 13 = 0 0 + 1x = 0 + 13 1x = 0 + 13 Combine like terms: 0 + 13 = 13 1x = 13 Divide each side by '1'. x = 13 Simplifying x = 13
| -22+2n=-8(3n+7) | | 5x+3y-4=30 | | log(7-12x)=2 | | 1+3y-y=y-4+2y | | 5y+3y-4=30 | | 6.2x+7.1x-y= | | Y=40x+-16x^2 | | .4y+7.96=2.24 | | (x+4y^2)dy+(y+x^2)dx=0 | | 28x^2-9x-1=0 | | 3x+13=-3x+73 | | (2v+14)(v^2-8v+12)=0 | | 14t+15=10t+31 | | 8x-1=642x | | 2t-7=t+2 | | z^2+(4+i)*z-6+6i=0 | | 6h+20=720 | | 2b-50+b+2b-2+30+b-25+44+b-22=360 | | 2n-15=45 | | -3(4+2)=4-22 | | 4n+12=7n+9 | | 3w-23+3w-33+4w+4w-46+49+3w-39+61=360 | | 2x*2x-9x+2=0 | | 2x+2(3x+1)+3x-1=7x+1 | | 6x+6=6x-5 | | 2x+45=x-32 | | 60.5+90+x=180 | | 3w-23+3w-33+4w-46+3w-39+49+61=360 | | 6(x+1)-(p+1)=6x+3 | | 7k^3+2x=0 | | 12s=16+6s+19 | | 7y-9=-2 |